SEGMENTASI NASABAH BERDASARKAN GAYA HIDUP PADA UNIT USAHA SYARIAH DI SURABAYA - Risky Amalia Hanum; Basuki Rahmat; Yudi Sutarso (STIE Perbanas Surabaya, 2012)
The research tried to examine the factors that are formed in the customers of syariah banking Unit in Surabaya, to examine the customers segmentation in Surobaya based on the lifestyle,to identify the profile from each customers segment in Surabaya banking unit based on lifestyle, to examine the difference of characteristic among segments which are formed based on lifestyle factor of syariah banking unit customers in Surabaya and to test the difference of characteristic among segments which are formed based on demographic variable on the customers of syariah bonking unit in Surabaya. The researcher distributed 300 and 200 questionnaires were gathered and analyzed. Factor analysis, cluster analysis, cross tab, and chi-square analysis were employed for analyses. It showed that there were nine factors such as brand tryer factor, affecting factor, sensitivity of price factor, sport interest factor, internet user factor, optimism factor, compulsive housekeeper factor, electronic banking user factor and credit assumption factor. The segment formed yields four clusters such as technology user segment, credit user segment, electronic banking user segment, brand user segment. As for the result of chi-square test shows that there are differences in characteristic among segment which are formed based on customers lifestyle factor in syariah banking unit in Surabaya. There was a difference of characteristic among gender, age, education, occupation and duration of being customers.